How Did Kachok Dumpsite in Kisumu City Develop into a Crisis? - Awuor, Frankline Otiende; Nyakinya, Belinda; Oloo, John; Oloko, Michael; Agong’, Stephen Gaya (My University, 2019)
Municipal solid waste management is one of Kenya’s most pressing environmental problems evidenced by the many overflowing dumpsites with their associated environmental and health hazards. Their growth is precipitated by the rapid urbanization and changing lifestyles in the country. In Kisumu County, this problem is encapsulated in Kachok dumpsite which is less than 2 km from the center of the central business district of Kisumu City. This work chronicles and discusses the history of Kachok dumpsite with the aim of highlighting its historical causation and policy implications to remedy future crises. Data was collected through in-depth interviews of key informants, observation, and reviews of the internet, and print media and analyzed through critical and content analysis. Findings indicate that the dumpsite’s crisis was occasioned by the failure of management to look for alternative land in time, failure to plan the site for onsite waste handling and poor dumpsite and waste management. Policy recommendations on dumpsite site location, dumpsite and solid waste management, and monitoring and evaluation of landfills have been suggested to avert future crises.